Can Our Church Live? - Mann, Alice, (Rowman & Littlefield Publishers, 2000)
Nothing on earth lives forever—not even congregations. Alban Institute senior consultant Alice Mann explains how the natural life cycle of a congregation, as well as other internal and external factors, can produce a congregation that is in real trouble. She then offers hope for congregations that want to change. Practical options for congregations, leadership challenges for laity and clergy, and ways to work with denominations are detailed and engaging discussion questions provide a basis for congregational planning